On the composition gradient of steel/Invar functionally graded material manufactured by wire-based direct energy deposition - Wang, Jun; Biswal, Romali; Chen, Guangyu; Pardal, Goncalo; Lu, Yao; Ding, Jialuo; Williams, Stewart W. (Elsevier, 2024)
This study utilized double-wire plasma arc direct energy deposition to produce functionally graded materials (FGMs) with two transition designs, abrupt (AT) and gradual (GT), from Er90s steel to Invar. The study systematically compared the transition in chemical composition, microstructure, phase evolution, thermal stress, and mechanical performance. Both FGM types exhibited a band structure in the Er90s section and coarse columnar grains in the Invar section, with the AT deposit showing a 1 mm thick, defect-free interface and the GT deposit having an 18 mm thick transition region with distinct boundaries. It revealed diverse microstructures across the transition zones, including fine ferrite, martensite with minor retained austenite (RA), coarse columnar austenite with martensite dendrites, and single FCC austenite. The GT sample uniquely featured a microstructure of martensite laths inside prior austenite decorated by RA semicontinuous network, with a crack detected due to dilatational stresses from martensite transformation. Hardness was similar in both FGM types, with higher values at the interfaces, especially in the GT FGM. The GT FGM demonstrated higher strength but lower ductility compared to the AT FGM, with failure occurring in the Invar portion for both. Thermal stress modelling indicated smoother stress transitions in the GT sample but no significant performance differences between Er90s and Invar. This study showcases the effectiveness of double-wire plasma arc DED in producing steel/Invar FGMs with varying composition gradients. It also underscores the importance of selecting the right mixing ratio for Er90s/Invar FGM deposits to avoid cracking and deterioration of properties in the gradient area.
Keywords: 40 Engineering; 4016 Materials Engineering; 4014 Manufacturing engineering; Composition gradient; Functionally graded material; Wire-based direct energy deposition; Microstructure evolution; Properties